Characterization and conservation of farm animal genetic resources: Current status in sub-Saharan Africa - Rege, J.E.O. (Canadian Foundation for the Conservation of Farm Animal Genetic Resources, 1997)
This paper describes the major activities in sub Saharan Africa in the area of characterization and conservation of Animal genetic resources. Rege (1994) summarised the major animal genetic resources activities, primarily breed characterization and genetic improvement programmes, which are being implemented by NARS in Africa. The present paper focusses on-going activities in the programme of ILRI and its partners. The activities described are summarised at the end of the paper.